Conditional flux balance analysis toolbox for python: application to research metabolism in cyclic environments - Páez-Watson, Timothy; Hernández Medina, Ricardo; Vellekoop, Loek; van Loosdrecht, Mark C.M.; Wahl, S. Aljoscha (Bioinformatics Advances, 2024)
We present py_cFBA, a Python-based toolbox for conditional flux balance analysis (cFBA). Our toolbox allows for an easy implementation of cFBA models using a well-documented and modular approach and supports the generation of Systems Biology Markup Language models. The toolbox is designed to be user-friendly, versatile, and freely available to non-commercial users, serving as a valuable resource for researchers predicting metabolic behaviour with resource allocation in dynamic-cyclic environments.
CRIS-Team Scopus Importer:2025-02-04